2010
DOI: 10.4015/s1016237210001906
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Subacute Oral Toxicity Tests of Sintered Dicalcium Pyrophosphate on Ovariectomized Rats for Osteoporosis Treatment

Abstract: Sintered dicalcium pyrophosphate (SDCP) is a synthetic pyrophosphate analog that could be utilized in the treatment for osteoporosis. In this study, an ovariectomized rat model is used to evaluate the systematic toxicity of orally administered SDCP relative to its effects on bone mass. Ovariectomized Wistar rats were treated with experimental medication with different dosing strategies (0.5 mg/kg five days weekly, and 2.5 mg/kg once weekly) for once (acute oral toxicity test) and four weeks (subacute oral toxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
(21 reference statements)
0
8
0
Order By: Relevance
“…The processes of angiogenesis and osteogenesis are coupled during bone regeneration 39 . Blood vessels not only transport oxygen and nutrients but also play an important role in bone formation and remodeling by mediating the interaction between osteoblasts, osteocytes, osteoclasts, and vascular cells 40 . These data confirmed that hypoxia preconditioned BMSCs had a better angiogenic capacity in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…The processes of angiogenesis and osteogenesis are coupled during bone regeneration 39 . Blood vessels not only transport oxygen and nutrients but also play an important role in bone formation and remodeling by mediating the interaction between osteoblasts, osteocytes, osteoclasts, and vascular cells 40 . These data confirmed that hypoxia preconditioned BMSCs had a better angiogenic capacity in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…SDCP, which can reduce bone resorption, should be useful for the treatment of osteoporosis [ 22 ]. Although previous acute and subacute oral toxicity studies have reported that the ingestion of SDCP did not show deleterious effects on test subjects [ 21 ], the long-term oral toxicity has not been tested. Regarding the potential toxic effects of SDCP, we found no clinical signs of toxicity and no changes in food consumption, hematology, or necropsy attributable to the oral administration of SDCP.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that elcatonin has an inhibitory effect on appetite, and a similar finding was also observed in rats treated with ALN [ 24 ]. Previous acute and subacute oral toxicity studies showed that rats treated with SDCP had a relatively lower weight than those of OVX rats [ 21 ], which reveals that SDCP may also inhibit appetite. In spite of the significant differences in body weight, there was no significant change in the femur volume, length, or width in the OVX + SDCP and OVX + ALN groups when compared with the OVX group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations